2009
DOI: 10.1080/08923970802520701
|View full text |Cite
|
Sign up to set email alerts
|

Modulatory effect of hydrogen peroxide on tumoral lymphocytes proliferation

Abstract: BW 5147 (murine lymphoma cell line). We analyzed the effect of H2O2 in cell proliferation testing nitric oxide and apoptosis. Enzymes involved in the regulation of H2O2 levels as superoxide dismutase (SOD) and peroxidase (PER) were analyzed. H2O2 exerted a biphasic effect. The inhibitory effect of H2O2 was related to the activation of the ERK and P38 pathway, NO production and apoptosis. The high proliferation was associated with a low level of H2O2 related to a low SOD and a high PER activities. Drugs capable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 25 publications
1
26
0
Order By: Relevance
“…It is already known that the activation of macrophages induces an increase in molecules which can conduce cells to apoptosis; among these molecules, TNF-α and H 2 O 2 can be mentioned. In this respect, it was demonstrated that H 2 O 2 induces lymphocytes to late and early apoptosis, (19) also TNF-α is capable of producing cell death by apoptosis. (20) Activation of macrophages phagocytosis was also observed with other compounds and plant extracts.…”
Section: Discussionmentioning
confidence: 98%
“…It is already known that the activation of macrophages induces an increase in molecules which can conduce cells to apoptosis; among these molecules, TNF-α and H 2 O 2 can be mentioned. In this respect, it was demonstrated that H 2 O 2 induces lymphocytes to late and early apoptosis, (19) also TNF-α is capable of producing cell death by apoptosis. (20) Activation of macrophages phagocytosis was also observed with other compounds and plant extracts.…”
Section: Discussionmentioning
confidence: 98%
“…In normal lymphocytes, however, the antiproliferative action exerted by the extract appeared to be related to peroxidase activity, as the EC 50 values for both effects were in the same range. It has been demonstrated previously that normal lymphocytes contain more H 2 O 2 than BW 5147 cells under basal conditions (Davicino et al , ); these higher concentrations of H 2 O 2 may therefore allow the cells to proliferate so that when the extract exerted peroxidase activity, scavenging H 2 O 2 , an inhibition of cell proliferation occurred. There is evidence indicating that H 2 O 2 and the superoxide anion can influence the growth and death of cells.…”
Section: Discussionmentioning
confidence: 98%
“…It has been shown previously that BW 5147 cells maintain low levels of H 2 O 2 so peroxidase activity could not contribute to the antiproliferative effect, as shown in this study. Moreover, an increase of H 2 O 2 contributed to the antiproliferative action of an extract of Larrea divaricata in the same cell line (Davicino et al , ). So in BW 5147 cells, it is an increase in H 2 O 2 that produces inhibition of cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…MTT is a membrane‐permeable tetrazolium salt, which is reduced to formazan by superoxide anion in living cells, 18,23 either in the mitochondria or in intracellular vesicles identified as endosomes and lysosomes 24 . We have already demonstrated that L. divaricata decoction produces mitochondrial superoxide 10 . We believe that the high levels of reduced MTT could be indicating an increased production of superoxide anion 25 …”
Section: Discussionmentioning
confidence: 98%
“…7,8 Moreover, fractions isolated from the decoction induced the activation of the innate immune system in vitro. 9 On the other hand, Davicino et al [10] showed the effect of an aqueous extract of this plant on proliferation, apoptosis, activation of Mn 2+ -dependent superoxide dismutase, and production of H 2 O 2 and nitric oxide in the tumour cell line BW5147.…”
Section: Introductionmentioning
confidence: 99%